2021
DOI: 10.1111/cobi.13803
|View full text |Cite
|
Sign up to set email alerts
|

Cooling of bat hibernacula to mitigate white‐nose syndrome

Abstract: Cooling historically unimportant hibernacula provides bats with critical habitat and is an important tool for combating whitenose syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
45
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(47 citation statements)
references
References 39 publications
2
45
0
Order By: Relevance
“…Decreasing temperature reduces the growth rate of the fungus and decreases energy expenditure in bats 55 , but bats in this captive experiment that could choose their temperature condition generally avoided the coldest condition 38 . Adjustments to hibernaculum microclimates have been proposed as a potential habitat modification aimed to provide beneficial conditions for bat species that have suffered substantial declines 22 , 24 , 35 . We caution that bat hibernation is a complex, multidimensional balancing act that warrants different solutions for different individuals and species 27 , 38 , 39 , 56 58 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Decreasing temperature reduces the growth rate of the fungus and decreases energy expenditure in bats 55 , but bats in this captive experiment that could choose their temperature condition generally avoided the coldest condition 38 . Adjustments to hibernaculum microclimates have been proposed as a potential habitat modification aimed to provide beneficial conditions for bat species that have suffered substantial declines 22 , 24 , 35 . We caution that bat hibernation is a complex, multidimensional balancing act that warrants different solutions for different individuals and species 27 , 38 , 39 , 56 58 .…”
Section: Discussionmentioning
confidence: 99%
“…We designed the experiment to determine behavioral selection of specific temperature and humidity conditions. Most natural hibernacula have a range of temperature and humidity 29 and behavioral selection by bats of beneficial microclimates would be necessary if management strategies of providing thermal refugia are to succeed 22 , 35 . We hypothesized that pre-hibernation body condition, specifically fat mass and stress indicator (measured by fur cortisol) would be related to disease outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Current efforts and tools for climate adaptation therefore remain far too limited to conserve the diversity of species and communities that will be harmed by climate change. In this context, we greatly appreciate Meierhofer et al.’s essay noting that the techniques we recently described for manipulating underground environments to conserve bats threatened by an invasive pathogen (Turner et al., 2022) could also be applied to protect other subterranean species from the worst effects of climate change.…”
mentioning
confidence: 99%
“…In Turner et al. (2022), we examined how hibernacula microclimates modify bat responses to white‐nose syndrome (WNS), a deadly infectious disease that has caused widespread, precipitous declines in several hibernating bat populations across eastern North America (Cheng et al., 2021). We found that, in the 8 years following mass mortality and pervasive regional contamination of hibernacula, 4 of the 5 bat species we studied increased or were found in higher numbers in hibernacula that were relatively colder or drier or both (i.e., hibernacula with midwinter temperatures of 3–6 °C and water vapor pressure deficits of 1–1.6 kPa).…”
mentioning
confidence: 99%
See 1 more Smart Citation